Ethnography as Commentary Writing from the Virtual Archive - Fabian, Johannes (Duke University Press, 2008)
The Internet allows ethnographers to deposit the textual materials on which they base their writing in virtual archives. Electronically archived fieldwork documents can be accessed at any time by the writer, his or her readers, and the people studied. Johannes Fabian, a leading theorist of anthropological practice, argues that virtual archives have the potential to shift the emphasis in ethnographic writing from the monograph to commentary. In this insightful study, he returns to the recording of a conversation he had with a ritual healer in the Congolese town of Lubumbashi more than three decades ago. Fabian's transcript and translation of the exchange have been deposited on a website (Language and Popular Culture in Africa), and in Ethnography as Commentary he provides a model of writing in the presence of a virtual archive.